2018
DOI: 10.1097/qai.0000000000001682
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Cost-Effectiveness of a Demand Creation Intervention to Increase Uptake of Voluntary Medical Male Circumcision in Tanzania: Spending More to Spend Less

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Any discrepancies were resolved at the site using the source data. Costing data for the intervention were collected and are reported elsewhere [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Any discrepancies were resolved at the site using the source data. Costing data for the intervention were collected and are reported elsewhere [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Eleven studies presented cost data [14,25,[36][37][38][39][40][41][42][43][44], three of which were related to articles included in the main effectiveness review. Studies were published between 2012 and 2018 and took place in Kenya [38,41], South Africa [39,42,43], Tanzania [44], Uganda [36,37,40], and Zimbabwe [14,25]. Descriptions of included cost studies and their outcomes are presented in Table 5.…”
Section: Costsmentioning
confidence: 99%
“…Descriptions of included cost studies and their outcomes are presented in Table 5. Seven of the included studies assessed community-based interventions [14,36,[40][41][42][43][44], two assessed school-based interventions [25,39], and two assessed facility-based interventions [37,38]. Generally, cost studies showed that service delivery interventions may create economies of scale and efficiencies when implemented widely.…”
Section: Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategies Kenya has used to achieve the national target of circumcising 80% of the country’s adult males [ 27 ] have routinely overlooked SCY who do not access health services through traditional channels [ 27 , 28 ]. Programs which employ innovative and locally-tailored approaches to youth and hard-to-reach populations have shown higher circumcision rates, more efficient resource utilization and increased cost-savings [ 29 32 ].…”
Section: Introductionmentioning
confidence: 99%